solving for t

I know this incorrect but not sure what to do.

-1/4t3 =8

-1/4=8t3

-1/32=t3



So your expression is:

\(\displaystyle - \dfrac{1}{4t^3} \ = 8\)

\(\displaystyle t^3 = - \dfrac{1}{32} = - 2^{-5}\)

\(\displaystyle \displaystyle{t = -2^{\left [-\frac{5}{3}\right ]}}\)
 
So your expression is:

\(\displaystyle - \dfrac{1}{4t^3} \ = 8\)

\(\displaystyle t^3 = - \dfrac{1}{32} = - 2^{-5}\)

\(\displaystyle \displaystyle{t = -2^{\left [-\frac{5}{3}\right ]}}\)


Yes up until \(\displaystyle = - 2^{-5}\) Don't understand this part where -5 came from

\(\displaystyle = - 2^{-5}\)

\(\displaystyle \displaystyle{t = -2^{\left [-\frac{5}{3}\right ]}}\)
 
Last edited:
Yes up until \(\displaystyle = - 2^{-5}\) Don't understand this part where -5 came from

\(\displaystyle = - 2^{-5}\)

\(\displaystyle \displaystyle{t = -2^{\left [-\frac{5}{3}\right ]}}\)

\(\displaystyle 2^5 \ = \ 32\) → \(\displaystyle \dfrac{1}{32} \ = \ 2^{-5}\)
 
Could you explain the procedure of what is happening a bit more, is there algebra, indices rules going on there?
 
I'm assuming you're still confused about where the 2^(-5) came from. Think about what negative exponents mean. n^(-1) can be rewritten as 1/n, so what does n^(-2) mean? Apply that same logic to 2^(-5). Once you have your new way of writing it, do you see that term in your original equation? Then when you get to t^3 = 2^(-5), you can simplify by taking the cube root of both sides. Like so:

\(\displaystyle t=\sqrt[3]{2^{-5}}\)

And since n^(1/3) means the same thing as the cube root of n, do you see why you can rewrite that as t = 2^(-5/3)?
 
I'm assuming you're still confused about where the 2^(-5) came from. Think about what negative exponents mean. n^(-1) can be rewritten as 1/n, so what does n^(-2) mean? Apply that same logic to 2^(-5). Once you have your new way of writing it, do you see that term in your original equation? Then when you get to t^3 = 2^(-5), you can simplify by taking the cube root of both sides. Like so:

\(\displaystyle t=\sqrt[3]{2^{-5}}\)

And since n^(1/3) means the same thing as the cube root of n, do you see why you can rewrite that as t = 2^(-5/3)?


\(\displaystyle t=\sqrt[3]{2^{-5}}\)

Ya that make sense now, I just couldn't picture what was happening.

Thanks you
 
Top